Apical barrier technique using MTA: report of two cases (Health Renaissance, 2012)
Open apices of pulpless immature teeth have always posed a problem as they need to be sealed before they are obturated. In recent years MTA has gained popularity as it provides a single step apical plug and thus helps in apexification. This article reports two cases which were successfully treated with MTA which had open apices. Health Renaissance; September-December 2012; Vol 10 (No.3);239—241 DOI: http://dx.doi.org/10.3126/hren.v10i3.7054